Nothing beats taste or convenience: a national survey of where and why people buy sugary drinks in Australia. (8th June 2020) - Dono, Joanne; Ettridge, Kerry; Wakefield, Melanie; Pettigrew, Simone; Coveney, John; Roder, David; Durkin, Sarah; Wittert, Gary; Martin, Jane; Miller, Caroline
Abstract: Objective : There is limited knowledge of what influences sugary drink purchasing decisions in the Australian population. This study aimed to identify the most common locations and reasons across different demographic groups for purchasing sugary drinks in Australia. Methods : A total of 891 respondents (who purchased sugary drinks for personal consumption at least occasionally) from a broader national population telephone survey of Australian adults conducted in 2017 (n=3, 430) were included in the analysis. Results : 'Taste' was a ubiquitous reason for purchase (94%) and the majority also agreed with 'easily available' (76%). Males, younger people and people of lower socioeconomic status (SES) were significantly more likely to agree that sugary drinks were 'cheap' and 'better value than water'. Furthermore, males and younger people were more likely to report buying sugary drinks because they were 'part of a meal deal'. The most common purchase locations were supermarkets (56%), followed by convenience stores (19%) and food or entertainment venues (17%). Conclusion : Taste is paramount in decisions to purchase sugary drinks, and widespread availability and value for money support consumption. Implications for public health : Policies and interventions targeting point‐of‐sale sugary drink purchasing decisions among the most 'at risk' consumers are warranted.